(untitled) (Journal of Partial Differential Equations, 2019)
The paper studies the stability of weak solutions of a nonlinear heat equation with degenerate on the boundary. A new kind of weak solutions are introduced. By the new weak solution, the stability of weak solutions is proved only dependent on the initial value.